Afternoon cortisol provides a link between self‐regulated anger and peer‐reported aggression in typically developing children in the school context. Issue 6 (22nd May 2017) - Oberle, Eva; McLachlan, Kaitlyn; Catherine, Nicole L.A.; Brain, Ursula; Schonert‐Reichl, Kimberly A.; Weinberg, Joanne; Oberlander, Tim F.
Abstract: Aggression jeopardizes positive development in children and predicts social and academic maladjustment in school. The present study determined the relationships among anger dysregulation (a marker of emotion regulation), cortisol activity (a biomarker of stress), and peer‐nominated aggression in typically developing children in their everyday classroom setting ( N = 151, Mean age = 10.86, SD =.74). Salivary cortisol was collected at 09:15, 11:45, and 14:45 hr across 4 consecutive days. Children provided self‐reports of anger regulation; peers reported proactive and reactive aggressive behaviors. Hierarchical linear regression analyses, followed by a bootstrapping analysis identified basal afternoon cortisol as a significant mediator between anger regulation and peer‐reported aggression. More dysregulated anger significantly predicted lower afternoon cortisol, which in turn predicted increased peer‐reported aggression. These results align with previous research on links among hypocortisolism, emotional regulation, and behavior, and suggest a possible meditational pathway between emotion and behavior regulation via decreased afternoon cortisol levels.